Competitive preferences and status as an incentive: Experimental evidence - Gary Charness; David Masclet; Marie-Claire Villeval (Institute for the Study of Labor (IZA), 2010)
In this paper, we investigate individuals' investment in status in an environment where no monetary return can possibly be derived from reaching a better relative position. We use a real-effort experiment in which we permit individuals to learn and potentially improve their status (rank). We find that people express both intrinsic motivation and a taste for status. Indeed, people increase their effort when they are simply informed about their relative performance, and people pay both to sabotage others' output and to artificially increase their own relative performance. In addition, stronger group identity favors positive rivalry and discourages sabotage among peers.
Keywords: C91; C92; M54; D63; J28; J31; 330; Status seeking; rank; competitive preferences; experiment; Sozialer Status; Wettbewerb; Präferenztheorie; Leistungsmotivation; Test